Rasionalitas Motivasi Orang Tua Menyekolahkan Anaknya Di Madrasah Ibtidaiyah - Muhamad Akip; Mita Safitri; Taufik Mukmin; Sujarwo (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2023)
The purpose of this study was to find out the rationality of the motivation and expectations of parents to send their children to Madrasah Ibtidaiyah (MI), on average, parents seek and send their children to quality and quality institutions so that their children's education in the future can be guaranteed. This research is included in field research (Fied Research) with a qualitative descriptive approach. Data collection is done by observation, interviews and documentation. The results of this study suggest that the rationale for parents' motivation to send their children to Madrasah Ibtidaiyah Nur Riska Lubuklinggau is that there is a balance between worldly and hereafter lessons, many excellent programs, close proximity, affordable costs, more effective learning, adequate facilities, parental background, and finally more religious learning. As for the hopes of parents after sending their children to MI Nur Riska Lubuklinggau, there are also several of them, children can become hafidz of the Koran, children can understand religious and general knowledge, can improve children's morals, can become pious and pious children. supported by its flagship program Dhuha prayer every day, tadarus every morning, smart and motivation before studying, tahfidz quran, tahfidz hadith and daily prayers, educative zakat, educational visits, SBNR (alms with nur riska), social activities, and finally getting to know the basics of science and going on pilgrimage supported by local content.